Circulating microRNAs predispose to takotsubo syndrome following high-dose adrenaline exposure. Issue 7 (22nd June 2021) - Couch, Liam S; Fiedler, Jan; Chick, Giles; Clayton, Rory; Dries, Eef; Wienecke, Laura M; Fu, Lu; Fourre, Jerome; Pandey, Pragati; Derda, Anselm A; Wang, Brian X; Jabbour, Richard; et al.
Abstract: Aims : Takotsubo syndrome (TTS) is an acute heart failure, typically triggered by high adrenaline during physical or emotional stress. It is distinguished from myocardial infarction (MI) by a characteristic pattern of ventricular basal hypercontractility with hypokinesis of apical segments, and in the absence of culprit coronary occlusion. We aimed to understand whether recently discovered circulating biomarkers miR-16 and miR-26a, which differentiate TTS from MI at presentation, were mechanistically involved in the pathophysiology of TTS. Methods and results : miR-16 and miR-26a were co-overexpressed in rats with AAV and TTS induced with an adrenaline bolus. Untreated isolated rat cardiomyocytes were transfected with pre-/anti-miRs and functionally assessed. Ventricular basal hypercontraction and apical depression were accentuated in miR-transfected animals after induction of TTS. In vitro miR-16 and/or miR-26a overexpression in isolated apical (but not basal), cardiomyocytes produced strong depression of contraction, with loss of adrenaline sensitivity. They also enhanced the initial positive inotropic effect of adrenaline in basal cells. Decreased contractility after TTS-miRs was reproduced in non-failing human apical cardiomyocytes. Bioinformatic profiling of miR targets, followed by expression assays and functional experiments, identified reductions of CACNB1 (L-type calcium channel Cav β subunit), RGS4 (regulator of G-protein signalling 4), and G-protein subunit Gβ (GNB1) as underlying these effects. Conclusion: miR-16 and miR-26a sensitize the heart to TTS-like changes produced by adrenaline. Since these miRs have been associated with anxiety and depression, they could provide a mechanism whereby priming of the heart by previous stress causes an increased likelihood of TTS in the future. Graphical Abstract: